2019
DOI: 10.1111/ppl.13000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADP‐malic enzyme activity by H2S and NO in sweet pepper (Capsicum annuum L.) fruits

Abstract: NADPH is an essential cofactor in many physiological processes. Fruit ripening is caused by multiple biochemical pathways in which, reactive oxygen and nitrogen species (ROS/RNS) metabolism is involved. Previous studies have demonstrated the differential modulation of nitric oxide (NO) and hydrogen sulfide (H2S) content during sweet pepper (Capsicum annuum L.) fruit ripening, both of which regulate NADP‐isocitrate dehydrogenase activity. To gain a deeper understanding of the potential functions of other NADPH‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 83 publications
1
31
0
Order By: Relevance
“…Our data mostly confirm those previously found for other California-type pepper varieties [46]. Recent data report that pepper fruit NADP-DHs are not only influenced by ripening in the Melchor variety [8], but also by NO through diverse PTMs [87,88]. Moreover, it was also found that NADP-DHs are involved in the response of sweet pepper plants to stress exerted by high Cd levels [89].…”
Section: The Ripening Stage and The Capsaicinoids Content Alter The Msupporting
confidence: 91%
“…Our data mostly confirm those previously found for other California-type pepper varieties [46]. Recent data report that pepper fruit NADP-DHs are not only influenced by ripening in the Melchor variety [8], but also by NO through diverse PTMs [87,88]. Moreover, it was also found that NADP-DHs are involved in the response of sweet pepper plants to stress exerted by high Cd levels [89].…”
Section: The Ripening Stage and The Capsaicinoids Content Alter The Msupporting
confidence: 91%
“…NADPH-generating enzymes maintain redox state and support antioxidant enzymes, such as GR, as well as O 2 •− and NO generation by RBOH and NOS-like activity, respectively. These NADP-DHs are differentially modulated by nitration/S-nitrosation: chloroplast FNR is inhibited by nitration, NADP-ICDH and NADP-ME are inhibited by both nitration and S-nitrosation [173], while G6PDH and 6PGDH appear unaffected [174].…”
Section: Regulatory Role Of No Ptms S-nitrosation and Nitration In Rmentioning
confidence: 99%
“…The role of NO and H 2 S along with that of Si was evaluated for the regulation of cadmium stress in plants (Kaya et al 2019b). Muñoz-Vargas et al (2019) have noticed inhibition of NADP-malic enzyme activity by H 2 S and NO in sweet pepper. Furthermore, the role of H 2 S was examined in regulating photosynthesis under overnight frost and daytime high light in avocado (Joshi et al 2019).…”
mentioning
confidence: 99%